Kebakaran di lahan rawa/gambut di Sumatera: masalah dan solusi: prosiding semiloka, Palembang, Sumatera Selatan, 10 - 11 Desember 2003 - Suyanto, S.; Chokkalingam, U.; Wibowo, P. (Center for International Forestry Research, 2004)
Sumatra has a large and persistent wetland/peatland fire problem. Perspectives differ on the source and nature of the problem. There have been large negative environmental and socio-economic impacts arising from the fires. At the same time, fire is a useful tool for wetland use, and there are increasing population and development pressures on the wetlands. There is an urgent and critical need to identify, assess and resolve the problem fires; and work towards sustainable development and conservation of wetland resources.This book documents the insights and perspectives of different stakeholders in the wetlands of Sumatra on the key fire issues and their possible solutions in four common settings - a) Plantation and estate crop development, b) Remaining protection and production forests, c) Deforested wetlands mainly subject to local community use, and d) Transmigration agricultural development. They look beyond the fires at the underlying issues that need to be tackled such as development policies, livelihood pressures and options, and viable alternatives to burning in the wetlands. It is hoped that these insights from the ground will be useful for policy makers, forest managers, plantation companies, development agencies and non-governmental organizations to understand and work towards resolving Sumatra’s wetland fire problem. Lessons from Sumatra are also relevant for other wetland regions of Indonesia.